Surgical Treatment of Ossifications of the Cervical Anterior Longitudinal Ligament: A Retrospective Cohort Study. Issue 5 (June 2021) - Glinski, Alexander von; Takayanagi, Ariel; Elia, Christopher; Ishak, Basem; Listmann, Mishan; Pierre, Clifford A.; Blecher, Ronen; Hayman, Erik; Chapman, Jens R.; Oskouian, Rod J.
Study Design: Retrospective cohort study Objectives: The study aims to evaluate anterior cervical discectomy and fusion (ACDF) in the treatment of patients with ossification of the anterior longitudinal ligament (OALL). Methods: We retrospectively reviewed cases performed at our institution between January 2015 and December 2018; adult (age ≥18 years) patients who underwent anterior cervical decompression and fusion in the presence of dysphagia and OALL. Ten patients (9 male, 1 female, mean age 64.4 years) with OALL who underwent ACDF were included. Charts were reviewed for demographics and comorbidities. Primary outcomes assessed were intra- and postoperative complications. Secondary outcomes were fusion rates, instrumentation failure, postsurgical instability/deformity, and readmission rates. Results: The average duration of symptoms prior to surgery was 12.3 months. All patients presented with dysphagia (mean Bazaz score 2.0). The average number of levels with OALL was 4.7 (±1.67). All patients underwent ACDF and 3 patients underwent additional posterior cervical fusion for kyphotic deformity correction or when extensive laminectomy was required. We did not encounter any intraoperative complications. Eight patients (72%) had solid fusion demonstrated on the lateral x-rays and no evidence of progressive kyphotic deformity. We did not encounter any instrumentation failure or loosening. Two patients developed recurrence of dysphagia (Bazaz scores 2 and 3 respectively). Conclusion: ACDF for OALL with dysphagia and concomitant myelopathy in our small series of 10 patients demonstrate good fusion and clinical outcomes. Larger studies will be necessary to determine the optimal treatment for patients with dysphagia due to OALL.